Analysis of Factors Influencing the Performance of Account Officers at PNM Kabanjahe Branch Through Employee Competency as an Intervening Variable - Ashadi Jamik Kurniadi; Agus Salim (Dinasti Publisher, 2025)
This study aims to examine whether recruitment and selection have a significant positive effect on the performance of Account Officers at PT PNM Kabanjahe Branch, either directly or through competency as an intervening variable. There are four variables used in this study: Recruitment (X1) and Selection (X2) as independent variables, Performance (Y) as the dependent variable, and Competency (M) as the intervening variable. This research is quantitative in nature. The research instrument used was a questionnaire distributed to the respondents. The sampling technique employed total sampling, where the entire population was used as the research sample. The research respondents consisted of 22 Account Officers at PT PNM Kabanjahe Branch. The results show that Recruitment (X1) has a positive but not significant effect on the Performance of Account Officers at PT PNM Kabanjahe Branch. Selection has a positive but not significant effect on the Performance of Account Officers at PT PNM Kabanjahe Branch. Competency has a positive but not significant effect on the Performance of Account Officers at PT PNM Kabanjahe Branch. Recruitment has a positive but not significant effect on the Competency of Account Officers at PT PNM Kabanjahe Branch. Selection has a positive but not significant effect on the Competency of Account Officers at PT PNM Kabanjahe Branch. Recruitment has a positive but not significant effect on the Performance of Account Officers at PT PNM Kabanjahe Branch through Competency. Selection has a positive but not significant effect on the Performance of Account Officers at PT PNM Kabanjahe Branch through Competency.